The Hotel Mirah Bogor's Product-Based Branding Strategy - Diyan Putranto; Marhanani Tri Astuti; Adi Sopyan; Anindita Gayatri; Barliani Dewi Setyawati; Albertus Banundoyo (East Asian Journal of Multidisciplinary Research, 2023)
Hotel occupancy rates fell to 12 percent during the height of the COVID pandemic. Bogor is a city of Meetings, Incentives, Conventions, and events (MICE), particularly for the hotel sector, and it is currently in a process of recovery following a pandemic. The public's altered behavior during the pandemic has influenced hotels' reassessment of their products. When it comes to the government sector, the usage of online and digital media has a profound impact on meeting attendees. Descriptive qualitative methodologies were used, specifically SWOT analysis, and data was gathered via a literature study and an examination of social media platforms.  The findings indicate that a strategy to strengthen hotel branding in Bogor as a MICE hotel and leisure on weekdays as an alternative target group is required in order to meet the demands of potential customers. In the era following the pandemic, a good marketing strategy will require the creation of new products and services, as well as the introduction of innovative approaches to existing ones.Hotel occupancy rates fell to 12 percent during the height of the COVID pandemic. Bogor is a city of Meetings, Incentives, Conventions, and events (MICE), particularly for the hotel sector, and it is currently in a process of recovery following a pandemic. The public's altered behavior during the pandemic has influenced hotels' reassessment of their products. When it comes to the government sector, the usage of online and digital media has a profound impact on meeting attendees. Descriptive qualitative methodologies were used, specifically SWOT analysis, and data was gathered via a literature study and an examination of social media platforms.  The findings indicate that a strategy to strengthen hotel branding in Bogor as a MICE hotel and leisure on weekdays as an alternative target group is required in order to meet the demands of potential customers. In the era following the pandemic, a good marketing strategy will require the creation of new products and services, as well as the introduction of innovative approaches to existing ones.